Analysis of different quality agarwood oil (aquilaria malaccensis) and sensory study - Erny Haslina, Abd Latib; M. S., Najib; Che Mohd Aizal, Che Mohd; Saiful Nizam, Tajuddin (UTeM, 2018)
Agarwood is increasing in demand in the global market due to the presence of resinous wood that is widely used as an ingredient in perfumes, aromatherapy and traditional medicines. The popularity comes with concern on its unique smell (woody) and quality adulteration. This paper presents the response between chemical compositions in agarwood oil, reflected on the reading of fabricated e-nose which is used for classification. Different quality of samples which were identified as pure and mixture agarwood oil were analyzed by using gas chromatography for chemical profiling. Reveals that common major compounds like 4-phenyl-2-butanone, β-agarofuran, 10- epi-γ-eudesmol and agarospirol were found in the pure sample. An electronic nose (E-nose) that consists of a sensor array is a device used to substitute human olfactory system. The sample was exposed to the sensor array for odor profile recognition. The collected dataset was normalized and analyzed using box plot for feature extraction. The result concludes that different chemical compound was able to produce a different pattern for electronic nose reading even though the odor profile is almost similar.